Comparison of laboratory methods for quantification of fiber in feedstuffs - Lourenço, Maria do Socorro N.; Messana, Juliana D.; Sader, Ana Paula de O.; Canesin, Roberta C.; Malheiros, Euclides B.; Castagnino, Pablo S.; Berchielli, Telma T. (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: Peter Van Soest proposed the conventional method of fiber analysis using neutral detergent fiber (NDF) and acid detergent fiber (ADF). The main advantage of this method is the precision of results; however, reagents are costly and laboratory work requires long runtime and labor. Objective: to compare analytical data from different methodologies used to assess NDF and ADF contents. Methods: means obtained with the conventional method were compared through Dunnett’s test (α = 5%) with values from alternative methods using autoclave as the digester system. A completely randomized design in a 4 x 2 factorial arrangement was used. Results: NDF content through alternative methods was assessed for Tifton 85 hay, babassu meal and sugarcane, whereas ADF was only determined for babassu meal. NDF and ADF did not differ (p ≥ 0.05) between non-sequential or sequential analysis for all the feedstuffs and methods studied, except for ADF in corn silage. Conclusion: alternative methodologies allow reducing operating costs and time but lack uniformity and accuracy for analyzing ADF in corn silage. Palavras chave: